Review of M. Papathanassiou's Διαδρομές και ταυτότητες περιπλανώμενων τεχνιτών: Δύο ζαχαροπλάστες στην Ευρώπη του 19ου αιώνα [Tramping artisans' routes and identities: Two journeymen-confectioners in nineteenth-century Europe] - Karakatsouli, Anna (Historein, 2013)
Maria Papathanassiou, Διαδρομές και ταυτότητες περιπλανώμενων τεχνιτών: Δύο ζαχαροπλάστες στην Ευρώπη του 19ου αιώνα [Tramping artisans' routes and identities: Two journeymen-confectioners in nineteenth-century Europe], Athens, Smili: 2012. 290 pp.